Development of performance-based wind engineering for residential structures: from concept to application - Dao, Thang Nguyen, author; Van de Lindt, John W., advisor; Chen, Suren, committee member; Bienkiewicz, Bogusz, committee member; Senior, Bolivar A., committee member (Colorado State University. Libraries, 2010)
The majority of buildings and approximately 90% of residential structures in North America are light-frame wood construction. Many of these structures are subjected to high winds along the eastern seaboard and Gulf Coast and as a result routinely suffer damage resulting in significant financial losses. Losses for residential wood construction during hurricanes occur for a variety of reasons, i.e. from different sources. These include sources such as (a) the failure of structure due to high wind loading; (b) water intrusion as a result of high uplift pressures on the roof system resulting in gaps or as a result of a loss of roof coverings and/or roof sheathing panels; and (c) debris impact from windborne debris. A relatively new paradigm in earthquake engineering is performance-based design (PBD). PBD is, by and large, felt by most to be a system-level philosophy that allows inclusion of system level behavior including the improvement in performance as a result of this assertion. However, in wind engineering most failures are understood to be at the component and sub-assembly level. This study outlines and demonstrates the development of performance-based wind engineering for residential structures based on losses to the owner. To date, this is the first time a mechanistic model has been used to develop fragilities for performance expectations related to all levels of performance: occupant comfort, continued occupancy, life safety, structural integrity, and manageable loss.
Covers not scanned.
Keywords: Wooden-frame houses -- Aerodynamics; Wind-pressure; Architecture, Domestic -- Gulf Coast (U.S.)